2002
DOI: 10.1159/000064121
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tobacco Smoke and Ventilation in 20 Social Venues in Perth, Western Australia

Abstract: The indoor air quality and ventilation systems of 20 indoor public venues in the Perth Metropolitan area were investigated. This included 4 licensed restaurants, 2 licensed sporting clubs, 6 coffee shops (including a smoking café in a non-smoking shopping centre), 5 taverns, 2 night-clubs and a major hotel. Indicators of tobacco smoke and ventilation were monitored, the ventilation system was inspected and the number of people engaged in smoking and not smoking were counted. Averaged levels of nicotine varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…These elevated CO 2 concentrations are evidence that ventilation rates are often below levels required to achieve acceptable indoor air quality, regardless of whether there is smoking in the venues or not. Our findings are supported by the ventilation study of Dingle et al (2002), and of the 20 venues the authors investigated, none of the owners reported using their ventilation systems to maintain acceptable indoor air quality, instead using them only for maintaining thermal comfort.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These elevated CO 2 concentrations are evidence that ventilation rates are often below levels required to achieve acceptable indoor air quality, regardless of whether there is smoking in the venues or not. Our findings are supported by the ventilation study of Dingle et al (2002), and of the 20 venues the authors investigated, none of the owners reported using their ventilation systems to maintain acceptable indoor air quality, instead using them only for maintaining thermal comfort.…”
Section: Discussionsupporting
confidence: 81%
“…Carrington et al (2003) sampled particulate matter and nicotine in 60 pubs in Greater Manchester, UK and found that pubs without designated smoking sections had the highest particle concentrations; that the presence of non-smoking sections reduced particle concentrations even in the smoking areas; that some exposure to elevated particle concentrations still occurred in the non-smoking areas; and that ventilation systems did not have a significant effect on the particle concentrations. Another study in Perth, Western Australia involved air quality measurements in 20 social venues that permitted smoking and found elevated carbon monoxide (CO) and particulate matter concentrations (Dingle et al, 2002). Also, the authors found lesser concentrations behind the bars than in the public seating areas, implying that most buildings were not well-mixed.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, higher PM levels were measured in the non‐smoking area than in the smoking area. The limited knowledge of patrons of the ventilation systems is likely to be an obstacle to any legal requirement for “adequate ventilation.” It suggests that this proposed measure for air quality improvement is not practical, which also has been observed in a study in Perth, Australia (Dingle et al., 2002).…”
Section: Discussionmentioning
confidence: 66%
“…Considering that 83% of establishments had one or more doorways open, and 39% had one or more windows open to allow a draft into the establishment, it is likely that natural ventilation did in fact influence concentrations, even though it was not possible to calculate the extent of it. Even so, expert opinion of the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE), in addition to empirical evidence, shows that mechanical ventilation cannot effectively remove ETS (AkbarKhanzadeh, 2003;Carrington et al, 2003;Dingle et al, 2002;Drope et al, 2004). This signifies that for the time being, smoking bans remain the only effective way to prevent ETS exposure (Samet et al, 2005).…”
Section: Discussionmentioning
confidence: 99%